From brief to boundary object: a framework for designing boundary infrastructure for learning across research and practice - Farrell, Caitlin C.; Resnick, Alison Fox; White, Terrenda; Arce-Trigatti, Paula; Penuel, William R.; Botchway, Kingsley (Frontiers in Education, 2025)
This paper introduces a framework aimed at designing equity-centered boundary infrastructure that supports learning at the intersection of research and practice. Drawing on sociocultural learning theory and influenced by a multi-district equity initiative, the framework outlines four interconnected design principles: contextual responsiveness, disruption of power dynamics, support for transformational learning, and attention to enactment. To demonstrate the framework’s application, we focus on the redesign of a traditional research tool, the research brief, reimagining it to foster transformational learning and support systems change. We conclude by exploring the implications of this framework for the design and study of boundary infrastructure.